SUSTAINABLE ACADEMIC SUPERVISION IN IMPROVING TEACHER COMPETENCE - Mawardi, Mawardi (Universitas Nurul Jadid, 2022)
This study aims to find out whether the competence of teachers at SMP Negeri 3 Sarolangun in compiling syllabus and learning implementation plans can be improved with continuous academic supervision. This type of research is school action research conducted at Sarolangun 3 Public Middle School in the 2021/2022 Academic Year with the research subject being 12 teachers at SMP N 3 Sarolangun and the object of research being teacher competency in compiling syllabus and lesson plans. Data collection methods used are observation, interviews and documentation. Meanwhile, to test the validity of the data is to use data triangulation. The results of the study can be concluded that with continuous academic supervision it is scientifically proven to be able to increase teacher competence in preparing syllabus and lesson plans at SMP Negeri 3 Sarolangun. This is proven by the increase in the number of good teacher syllabuses from 24.75% to 80% after academic supervision. In addition, the number of good quality lesson plans also increased from 18.92% to 70%. In addition, teachers can follow academic supervision well.